1997
DOI: 10.1038/ki.1997.361
|View full text |Cite
|
Sign up to set email alerts
|

Galactose-deficient IgA1 in sera of IgA nephropathy patients is present in complexes with IgG

Abstract: IgA1 proteins from sera of patients with IgA nephropathy (IgAN) are galactosylated to a lesser degree than those from healthy controls. The increased reactivity of intact or de-sialylated serum IgA1 with N-acetylgalactosamine (GalNAc)-specific lectins, Helix aspersa (HAA) and Caragana arborescens (CAA) and de-sialylated IgA1 with Helix pomatia (HPA) and Bauhinia purpurea (BPA) indicated that the Gal deficiency is in glycans located in the hinge region of IgA1 molecules. De-sialylated IgA from sera of 81 IgAN p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
268
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 280 publications
(277 citation statements)
references
References 54 publications
8
268
1
Order By: Relevance
“…This hypothesis is based on the observation that sialylated GalNAc cannot be galactosylated or otherwise modified by additional glycan residues. 39 29 we had hypothesized that another mechanism may be premature sialylation of the GalNAc residue. 9 We based this hypothesis on the observation that addition of SA to GalNAc prevents attachment of Gal to GalNAc 39 and thus precludes further growth of the glycan.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is based on the observation that sialylated GalNAc cannot be galactosylated or otherwise modified by additional glycan residues. 39 29 we had hypothesized that another mechanism may be premature sialylation of the GalNAc residue. 9 We based this hypothesis on the observation that addition of SA to GalNAc prevents attachment of Gal to GalNAc 39 and thus precludes further growth of the glycan.…”
Section: Discussionmentioning
confidence: 99%
“…Carbohydratespecific lectin analysis of O-glycoproteins can provide information on glycan composition and comparative differences between samples, such as those from healthy controls and patients with various disease states. We have successfully demonstrated this in the analysis of IgA1 O-glycans from patients with IgAN versus healthy controls and disease controls (13)(14)(15). This included proximal assessment of sites with galactose (Gal)-deficient O-glycans after digests with IgAspecific proteases (8).…”
mentioning
confidence: 99%
“…Aberrantly glycosylated IgA1, deficient in Gal in some of the O-glycans in the HR, in serum is rare in healthy individuals but is present at elevated levels in IgAN patients (13,15). This distinctive IgA1 is in circulating immune complexes (8,10,15) and in the glomerular deposits of IgAN patients (16,29). The absence of Gal apparently leads to the exposure of neoepitopes, including terminal and sialylated N-acetylgalactosamine (GalNAc) residues (9,10).…”
mentioning
confidence: 99%
“…The IgA1 found in the circulation and deposited in glomerular lesions was shown to be galactosedeficient, forming immune complexes with IgG or IgA1 [2,3]. Genome-wide association studies identified loci in the MHC, CFH/CFHR, HORMAD2 as well as other genes associated with IgA nephropathy [4].…”
Section: Introductionmentioning
confidence: 99%